Qualitative Exploration of Pharmacists’ Feedback Following the Implementation of an “Allergic Rhinitis Clinical Management Pathway (AR-CMaP)” in Australian Community Pharmacies - Cvetkovski, Biljana (Pharmacy (Basel), 2020)
Allergic Rhinitis (AR) is both a common and high burden disease, with the majority of AR sufferers purchasing suboptimal/inappropriate AR medication from community pharmacies. Unfortunately, it is still a challenge to translate the AR management guidelines that are available at both a global and national level into practice. This study aimed to explore the experiences and perceptions of community pharmacists with regards to the implementation of AR management guidelines in real-life everyday practice. This exploration took the form of a qualitative research study in which pharmacists were interviewed following the implementation of a guideline-driven AR management pathway in their pharmacies. Fifteen pharmacists from six pharmacies agreed to participate in a telephone interview. Five themes were identified that encompassed the sentiment of the pharmacists during the interviews: (1) impact of training on pharmacists’ approach to patients and AR management recommendations; (2) patient engagement and the importance of appropriate tools; (3) patient barriers to change in practice; (4) physical, logistical, and inter-professional barriers to change within the pharmacy environment; and (5) recommendations for improvement. The results of this study indicate that, following the implementation of an AR management pathway, pharmacists believe that their interactions with patients around their AR were enhanced through the use of appropriate tools and education. However, if optimal AR management is to be delivered within the community pharmacy setting, the undertaking needs to be collaborative with both pharmacy assistants and general practitioners.